Pengaruh komponen auditing terhadap kualitas audit (Studi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Nurul Aini Putri; Whetyningtyas , Aprilia; Ayu Susanti, Diah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This study aims to describe the practice of disclosure of audit quality provided by auditors to Indonesian manufacturing companies on the official website of the Indonesia Stock Exchange in 2016-2020. This study examines the effects of audit tenure, audit committee, audit capacity stress, audit fee and auditor switching on audit quality as measured by earnings surprise benchmark approach. The results showed that the audit tenure has no effect on audit quality with a significance level of 0.481, the audit committee has a positive effect on audit quality with a significance level of 0.001, audit capacity stress has a negative effect on audit quality with a significance level of 0.041, audit fee has a positive effect on audit quality with a significance level of 0.040, and auditor switching has no effect on audit quality with a significance level of 0.785 from manufacturing companies listed in Indonesia stock exchange.